EXERCICIO FISICO E FUNCIONAMENTO EXECUTIVO EM IDOSOS - Raquel de Sousa Milheiro (2017)
The aging process affects the performance of executive functioning of the elderly, associated with a decrease in the performance capacity of daily life activities, especially of instrumental ones. The objective of this study was to evaluate the contribution of a multicomponent exercise program in the executive functioning of the elderly. The sample of this study consisted of 15 elderly individuals, subdivided into a control group (sedentary) and an experimental group (active), and the subjects' participation was voluntary. The control group underwent a bi-weekly training lasting approximately 50 minutes for 2 months, including aerobic training, muscle strength, balance / coordination and flexibility, with the cognitive stimulation component as an increment. The Trail Making Test was used to evaluate the executive function in the pre and post-training moments. The results of the ANOVA RM did not show significant differences in the group * time interaction relative to the Trail Making Test (TMT-A: p = 0.069, η = B: p = 0.270, η = 0.124). However, there was an upward performance trend in TMT-A and TMT-B for the experimental group. These data suggest that physical exercise may be a potential aid in preventing executive functional decline in the elderly.